Rekaan Dan Pembangunan Penderia Kadar Aliran - Shahid, Mohd Hamadi (Universiti Sains Malaysia, 2006)
This project is being done to design and develop a system that can measure the flow rate of water inside a PVC pipe, 40mm in diameter. As a module the system was design and developed using a bilge pump design. For the microcontroller unit the system used a PIC16F877 chip. A propeller has been design as the tactile sensor for the system. The propeller will turn as water flows into the pipe. A microcontroller is used to count the revolutions of the propeller which is linear to the water flow rate in the pipe. For the purpose of counting the revolutions of the propeller an encoder circuit had been design. The circuit consists of an infra-red receiver and transmitter that is separated by a spinning slot. The encoder circuit will transmit series of low and high voltages which act as the input of the microcontroller. The microcontroller will then count the low voltage and divide it over the time it receive the signals. In the encoder circuit there are also a comparator and an amplifier circuit. These circuits’ purposes are to reduce the ripple and noise effect while increasing the voltage gain of the receiver signal. This is essential because the infra-red voltage signals are small and undetectable for the microcontroller. Lastly the output of the flow rate will be display in a LCD. The output will be in meter over second (m/s) example 0.24 m/s.